Adult male victims of female-perpetrated sexual violence: Australian social media responses, myths and flipped expectations - Loxton, April (International review of victimology, 2022)
In the era of #metoo, conversations regarding rape and sexual violence have received increased attention in mainstream media, giving voice to some of the many victims impacted by sexual assault. Despite the significant social upheaval this movement has given credence to, male victims of female-perpetrated sexual assault remain largely absent from Australian media. Adherence to strict representations of masculinity and femininity, often reinforced on social media, has resulted in cultural omission and problematic characterisations of both offenders and victims. International research has examined socially-constructed, gendered perceptions; however, Australian literature remains limited. This study examined what factors influence perceptions of male victims of female-perpetrated sexual violence, evaluated through Christie’s (1986) Ideal Victim/Offender framework. This mixed-method study analysed social media users’ comments on incidents of female-perpetrated sexual assault on men, presented in 28 Facebook posts, across 13 popular Australian newspapers. The findings identified a tendency of users to question victims’ masculinity, downplay harms experienced by male victims, or deny victimisation entirely. Furthermore, women were typecast as ‘fragile nurturers’ who did not have the capacity to offend, rejecting the possibility of male victims. Conclusions highlight the need for further Australian-based research and practical support, as male victims are more than simply an online myth.